Cancel Culture in South Korea's Entertainment Industry: Media Framing through the Lens of Deviance - Ramadhanty, Rizta Insani; Bajari, Atwar; Damayanti, Trie (Journal La Sociale, 2025)
The media has the power to carry out media framing and the public has the power to believe or not and participate in spreading‎ the results of the media framing or not, which will eventually lead to whether or not a cancel culture happens. The author wants‎ to analyze how Kumparan news articles apply framing to actor Kim Seon Ho's scandalous news which caused him to be exposed‎ to cancel culture, through journalistic analysis with The Sphere of Deviance theory by Daniel Hallin. The author conducted a‎ thematic analysis of 9 articles regarding the actor Kim Seon Ho scandal published by Kumparan in the period of 19 October 2021-‎‎22 October 2021 and resulted in 3 divisions of categories: positive (not supporting cancel culture), negative (supporting cancel‎ culture), and neutral. From the 9 news articles that were sampled, after the analysis, the writer produced the following data: 2‎ articles in the positive category, 1 article in the negative category, and 6 articles in the neutral category. Even though there is no‎ dominant framing in the article published by Kumparan regarding the Kim Seon Ho scandal, it can still be concluded that indeed‎ the media has power through media framing, as well as the public who have power over the information obtained from the‎ media (whether it is the result of media framing or not).